2022
DOI: 10.1039/d2gc01013e
|View full text |Cite
|
Sign up to set email alerts
|

Disproportionation of nitrogen induced by DC plasma-driven electrolysis in a nitrogen atmosphere

Abstract: Nitrogen disproportionation i.e. its simultaneous conversion to compounds of higher (NOx) and lower (NH3) oxidation states in a N2 DC plasma-driven electrolysis process with a plasma cathode is investigated. This...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 77 publications
1
9
0
Order By: Relevance
“…Muzammil et al [ 106 ] conducted a study on NF using a RGA reactor with tangential air input, driven by a 20 kHz AC power supply. The research found that lower SEI resulted in lower energy consumption, which is consistent with the conclusions of Pei et al [ 104 ] and Pattyn et al [ 91 ] The lowest energy consumption for NF was found to be approximately 0.67 MJ/mol.…”
Section: Recent Progress On Plasma Nfsupporting
confidence: 89%
See 1 more Smart Citation
“…Muzammil et al [ 106 ] conducted a study on NF using a RGA reactor with tangential air input, driven by a 20 kHz AC power supply. The research found that lower SEI resulted in lower energy consumption, which is consistent with the conclusions of Pei et al [ 104 ] and Pattyn et al [ 91 ] The lowest energy consumption for NF was found to be approximately 0.67 MJ/mol.…”
Section: Recent Progress On Plasma Nfsupporting
confidence: 89%
“…Pattyn et al [ 91 ] further investigated NF on the water surface using DC negative high voltage and studied the impact of adding water vapor to the nitrogen gas on the NF efficiency. They found that the best NF efficiency was achieved when adding 6–8 mol% water vapor, leading to lowest energy consumption of 61.6 MJ/mol.…”
Section: Recent Progress On Plasma Nfmentioning
confidence: 99%
“…Up to date, several catalytic systems have been demonstrated to have a potential of activating the super-strong N≡N triplebond, however their practical applications are yet to be explored [15][16][17] . N2 fixation into NH3 and NOy (NO, NO2, NO3, HNO3, HNO2, etc) has been reported in several plasmabased methods 10,12,18 . However, NOy are toxic to the environment.…”
mentioning
confidence: 99%
“…Up to date, several catalytic systems have been demonstrated to have a potential of activating the super-strong N≡N triple-bond, however their practical applications are yet to be explored (15)(16)(17). N2 fixation into NH3 and NOy (NO, NO2, NO3, HNO3, HNO2, etc) has been reported in several plasma-based methods (10,12,18). However, NOy are toxic to the environment.…”
mentioning
confidence: 99%